Data Collection in Fragile States Innovations from Africa and Beyond - Hoogeveen, Johannes; Pape, Utz (Springer International Publishing : Imprint: Palgrave Macmillan, 2020)
XXXI, 243 p. 58 illus., 52 illus. in color.